The Hero’s Journey: The Search for Identity from a Psychological, Mythological, and Astrological Perspective - Pannone, Silvia (Journal for the Study of Religion, Nature and Culture, 2007)
The intention of this paper is to ascertain whether the search for one’s highest and true being is inherent in humanity, how it can best be accomplished, and with what possible results. To this end, I have tried to identify common themes in psychology, myth, and astrology. This article begins with an exploration of the tenets of the main exponents of growth-oriented psychologies. I will then look at the role of mythology and its symbolic language. Consequently, I will analyse current developments within astrology and what the influence of psychology has been. Looking then for possible correlations between psychology and astrology, I will use, as my principal example, the archetype of the Self and the symbolism of the astrological sun. I will suggest that the theme most deeply-rooted in the human psyche is that of the hero’s journey and I will examine what this means in the different disciplines.